IMPLEMENTASI PROGRAM BANTUAN OPERASIONAL SEKOLAH (BOS) DI SEKOLAH DASAR NEGERI 12 PONTIANAK KOTA - Muhammad Firman Mauludy E.21109107 (FISIP Universitas Tanjungpura, 2013)
The writing ofthisarticleaimstodescribehow theimplementation ofBOSPrograminPublic Elementary School12PontianakCity, bothwithinthe organization, Interpretation, Applicationandconstraintsfaced.This studyincluded in thedescriptive studywithqualitativeanalyzesare focus on theprocess of organizing, intepretation, andapplicationsin the process ofimplementation ofthe BOSprogram.Thewriting ofthisarticleaims to describe, analyzeandassessthe process ofimplementation of theBOSprogram.Resultsofresearchinthe field showsthat theimplementation ofthe BOS programisrunning optimallyand in accordancewith the rulesandprocedures have been establishedandcontinue tocoordinatewith relatedparties, such astheparents,school committees, anddepartments ofeducation in bothlocal and centralso thatthe implementation ofthe BOS programwillrun properly. Keywords: Implementation of the BOS, BOS Organizing Implementation, Interpretation Program Implementation BOS, BOS Program Application Implementation